Evidence on the Effectiveness of Water, Sanitation, and Hygiene (WASH) Interventions on Health Outcomes in Humanitarian Crises: A Systematic Review. - Anita Ramesh; Karl Blanchet; Jeroen H J Ensink; Bayard Roberts (PLoS ONE, 2015)
Water, sanitation, and hygiene (WASH) interventions are amongst the most crucial in humanitarian crises, although the impact of the different WASH interventions on health outcomes remains unclear.To examine the quantity and quality of evidence on WASH interventions on health outcomes in humanitarian crises, as well as evaluate current evidence on their effectiveness against health outcomes in these contexts.A systematic literature review was conducted of primary and grey quantitative literature on WASH interventions measured against health outcomes in humanitarian crises occurring from 1980-2014. Populations of interest were those in resident in humanitarian settings, with a focus on acute crisis and early recovery stages of humanitarian crises in low and middle-income countries. Interventions of interest were WASH-related, while outcomes of interest were health-related. Study quality was assessed via STROBE/CONSORT criteria. Results were analyzed descriptively, and PRISMA reporting was followed.Of 3963 studies initially retrieved, only 6 published studies measured a statistically significant change in health outcome as a result of a WASH intervention. All 6 studies employed point-of-use (POU) water quality interventions, with 50% using safe water storage (SWS) and 35% using household water treatment (HWT). All 6 studies used self-reported diarrhea outcomes, 2 studies also reported laboratory confirmed outcomes, and 2 studies reported health treatment outcomes (e.g. clinical admissions). 1 study measured WASH intervention success in relation to both health and water quality outcomes; 1 study recorded uptake (use of soap) as well as health outcomes. 2 studies were unblinded randomized-controlled trials, while 4 were uncontrolled longitudinal studies. 2 studies were graded as providing high quality evidence; 3 studies provided moderate and 1 study low quality evidence.The current evidence base on the impact of WASH interventions on health outcomes in humanitarian crises is extremely limited, and numerous methodological limitations limit the ability to determine associative, let alone causal, relationships.